2018
DOI: 10.1002/ejp.1237
|View full text |Cite
|
Sign up to set email alerts
|

Parental chronic widespread pain and the association with chronic widespread pain in adult offspring: Family‐linkage data from the Norwegian HUNT Study

Abstract: The parent-offspring transmission of CWP is stronger in obese offspring (particularly when both parents have CWP). This study is the first to investigate the interaction between modifiable lifestyle factors, familial factors and CWP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…This nding is consistent with earlier studies of pain in the general population that reported an association between reduced HRQOL and experiencing pain [49]. One possible explanation of the strong negative effect of pain on the physical dimensions of HRQOL is that having persistent pain may affect daily activities such as the ability to exercise and participate in social activities [12,50]. These activities are important to the role as a parent of children at this age.…”
Section: Discussionsupporting
confidence: 90%
“…This nding is consistent with earlier studies of pain in the general population that reported an association between reduced HRQOL and experiencing pain [49]. One possible explanation of the strong negative effect of pain on the physical dimensions of HRQOL is that having persistent pain may affect daily activities such as the ability to exercise and participate in social activities [12,50]. These activities are important to the role as a parent of children at this age.…”
Section: Discussionsupporting
confidence: 90%
“…Vehof and Williams [93] suggested that the once evolutionary advantage of high pain sensitivity may have turned into a genetic predisposition to the neurobiological underpinnings of chronic pain. Parental CWP was shown to increase the risk of CWP in adult offspring, particularly if both parents had CWP, and offspring were obese [41]. Reviewing eight twin studies on CWP, six molecular genetic studies on CWP, and one epigenetic study, the findings by Kerr and Burri [42] suggested that genetic and unique environmental factors contributed to CWP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, parental chronic MSK pain is associated with increased occurrence of chronic MSK pain in adult offspring [44][45][46], with stronger associations observed when both parents have MSK pain [45; 76]. Furthermore, adults with a sibling with MSK pain have greater odds of experience MSK pain [76].…”
Section: Discussionmentioning
confidence: 99%